THE SOURCES OF FUNDING, PROCEDURE AND CHALLENGES OF INVESTMENT ACTIVITY AT OIL AND GAS ENTERPRISES OF UZBEKISTAN - Samiev Sardor Iskandarovich (Research Parks Publishers, 2021)
The article considers issues related to the sources, procedures and problems of financing investment activities in oil and gas companies of the country in several areas and draws appropriate conclusions.